2020
DOI: 10.1177/0954405420971081
|View full text |Cite
|
Sign up to set email alerts
|

Surface texture characterization of selective laser melted Ti-6Al-4V components using fractal dimension and lacunarity analysis

Abstract: The Selective Laser Melting (SLM) process based additive manufacturing has wide applications in medical, aerospace, defense, and automotive industries. To qualify the components for certain tribological applications, the characterization of surface texture is very important. But the applicability of traditional methods and parameters to characterize the surface texture were under evaluation. As the nature manufacturing the components were very different and complex, the unconventional surface characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…One notable advantage of this AM technique is its ability to directly fabricate intricate lenses or mirrors by customizing the material according to specific requirements [13][14][15] . Akhil et al demonstrated selective laser melting based additive manufacturing surface characteristics using the analysis of surface images 16 . However, AM Ti-6Al-4V ELI alloy is often treated as difficult to machine due to tool wear and generally requires an appropriate selection of process parameters 17 .…”
Section: Introductionmentioning
confidence: 99%
“…One notable advantage of this AM technique is its ability to directly fabricate intricate lenses or mirrors by customizing the material according to specific requirements [13][14][15] . Akhil et al demonstrated selective laser melting based additive manufacturing surface characteristics using the analysis of surface images 16 . However, AM Ti-6Al-4V ELI alloy is often treated as difficult to machine due to tool wear and generally requires an appropriate selection of process parameters 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the SLM forming process has unrivalled advantages in the processing of complex built-in channel structural parts. However, the mechanism of SLM process is extremely complicated due to the effects of many input parameters accompanied by appearance of the different non-equilibrium physical phenomenon, 21,22 the flow channel or the channel structure is still the difficulty to be overcome by SLM forming and receive critical attention. In order to improve the quality of its overhanging surface, by summarizing the scholars' research on metal overhanging structural parts by SLM, the main optimization methods can be divided into two categories: support-assisted structure forming and unsupported optimization.…”
Section: Introductionmentioning
confidence: 99%